2005
DOI: 10.1086/497899
|View full text |Cite
|
Sign up to set email alerts
|

Global Three‐dimensional Flow of a Neutron Superfluid in a Spherical Shell in a Neutron Star

Abstract: We integrate for the first time the hydrodynamic Hall-Vinen-Bekarevich-Khalatnikov equations of motion of a 1 S 0 -paired neutron superfluid in a rotating spherical shell, using a pseudo-spectral collocation algorithm coupled with a time-split fractional scheme. Numerical instabilities are smoothed by spectral filtering. Three numerical experiments are conducted, with the following results. (1) When the inner and outer spheres are put into steady differential rotation, the viscous torque exerted on the spheres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(141 citation statements)
references
References 79 publications
2
139
0
Order By: Relevance
“…Finally, a further coarse-graining of our model would correspond to theories of the HallVinen (Hall & Vinen 1956) and Bekharevich-Khalatnikov (Leggett 2006) type, i.e. to statistical theories of thermal superfluid turbulence (Henderson & Barenghi 2004;Peralta et al 2005Peralta et al , 2006Peralta et al , 2008Andersson, Sidery & Comer 2007;Sidery, Andersson & Comer 2008;Melatos & Peralta 2010). The mathematical difficulties involved in this coarse-graining are great, and our results could guide the relevant analyses.…”
Section: Introductionmentioning
confidence: 85%
“…Finally, a further coarse-graining of our model would correspond to theories of the HallVinen (Hall & Vinen 1956) and Bekharevich-Khalatnikov (Leggett 2006) type, i.e. to statistical theories of thermal superfluid turbulence (Henderson & Barenghi 2004;Peralta et al 2005Peralta et al , 2006Peralta et al , 2008Andersson, Sidery & Comer 2007;Sidery, Andersson & Comer 2008;Melatos & Peralta 2010). The mathematical difficulties involved in this coarse-graining are great, and our results could guide the relevant analyses.…”
Section: Introductionmentioning
confidence: 85%
“…Peralta et al [28,177] showed that, in the absence of magnetic fields, a sizeable axial counterflow develops which exceeds the threshold for the Donnelly-Glaberson instability in most of the star. The mutual friction force changes form and strength in those regions where the threshold is exceeded.…”
Section: Hydrodynamical Instabilitesmentioning
confidence: 99%
“…The force per unit length should then be calculated as an average over all angular directions. In following this procedure we neglect the effects of turbulence, which may arise in NS interiors (Peralta 2005;Peralta et al 2006;Andersson, Sidery & Comer 2007), possibly due to modes of oscillations of the superfluid that may be unstable in the presence of pinning (Glampedakis & Andersson 2009;Link 2012). In this case the vortex array is likely to form a complex tangle, that must, however, still be polarized due to the rotation of the star.…”
Section: Mesoscopic Pinning Forcementioning
confidence: 99%